2002
DOI: 10.2740/jisdh.13.99
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Liking for Sugar Solutions in Junior High School Students and Adults

Abstract: Liking for 4 levels of sucrose solution(2.5%,5.0%,10.0%,20.0%)and 3 kinds of sugar solution having different taste qualities of sweetness were investigated using sensory evaluation in junior high school students and adults(290 subjects).The questionnaire survey including affection,cognition,liking and consumption of sweets was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Conclusively, it might be said that females appreciated sweetness more than males did. Some studies suggested that females like low concentrated sucrose solution better than males do (Enns et al, 1979;Katou & Ikawa, 2002). But we think these results do not mean that females do not like sweetness.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Conclusively, it might be said that females appreciated sweetness more than males did. Some studies suggested that females like low concentrated sucrose solution better than males do (Enns et al, 1979;Katou & Ikawa, 2002). But we think these results do not mean that females do not like sweetness.…”
Section: Discussionmentioning
confidence: 48%
“…There are some results from sensory evaluation tests about sweet preferences with regard to age (de Graaf & Zandstra, 1999;Desor & Beauchamp, 1987;Enns et al, 1979;Katou & Ikawa, 2002;Zandstra & de Graaf, 1998). The reason why there are age-related differences in preferred sweetness can be found in the combination of both changes in physiology (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, studies of Zellner, Garriga-Trillo, Rohm, Centeno, and Parker (1999) and Parker et al (2003) claimed that American and Spanish Caucasians men preferred higher concentrations of sweet compared to women. Besides, other research also found that males did report greater liking for sweet foods (Conner & Booth, 1988;Katou & Ikawa, 2002;Tuorila & Mahlanmaki, 1985). These conflicting results may be due to the different methodology used in the studies.…”
Section: Discussionmentioning
confidence: 91%